Strategies for Translating Ecological Terms in the Quran into the Palembang Language - Syawaluddin Firdaus; Teguh Setiawan (Modality Journal: International Journal of Linguistics and Literature, 2025)
This study focuses on analyzing the translation strategies of ecological terms in the Qur'an into the Palembang Malay language. Many studies have been conducted on Palembang language translation, but none have specifically examined the strategies used. Meanwhile, this needs to be studied as practical knowledge for readers of translations to identify the objectives of the strategy, thereby facilitating the understanding of ecological concepts in the Qur'an. The results of the study show that the ecological terms found in the Qur'an include 46 data related to animals, 18 related to plants, and 25 related to geography. In the translation into Palembang, various linguistic forms are used with various strategies. Among Baker's 8 translation strategies, there are 5 strategies found in the translation of these ecological terms. These include the superordinate strategy (11 data), translation with more neutral/less expressive words (34 data), translation with cultural substitution (12 data), translation with equivalent words and explanations (29 data), and translation with paraphrasing using related words (2 data). These findings indicate that in the translation of ecological terms, emphasis is placed on strategies for clarity of meaning and cultural accessibility for Palembang readers. In this case, it can practically improve the accessibility and understanding of the community towards the regional translation of the Qur'an.